Efektivitas Antibakteri Senyawa Kurkumin terhadap Foodborne Bacteria: Tinjauan Curcuma longa untuk Mengatasi Resistensi Antibiotik - Anak Agung Ayu Dewi Sekarini; Ita Krissanti; Mas Rizky A. A. Syamsunarno (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2020)
Antibiotic resistance has negatively impacted the food safety with increasing number of resistant foodborne bacteria, especially foods from farm animals. Turmeric or Curcuma longa has curcumin as its main active component, which is known to have wide range biological activities and low toxicity. Curcumin shows better antibacterial effectiveness than C. longa extract in vitro and in vivo studies, so that has big potential as an alternative antibacterial because of its inexpensiveness, easy to find, and safe to use. However, curcumin is hydrophobic, that makes it hard to dissolve in the body, thus it needs other formulation to enhance its bioavailability. This review discusses the antibacterial activity of curcumin against foodborne bacteria including various formulations, mechanisms, and the toxicity of curcumin.